Enhancement of Solubility and Dissolution Rate of Poorly Soluble Antihypertensive Drug using Solid Dispersion Technique (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: To develop and evaluate solid dispersions of carvedilol to enhance solubility and dissolution rate using different hydrophilic carriers. Materials and Methods: Estimation of carvedilol was carried out using validated UV method. Solubility studies of pure drug were evaluated in the presence of different hydrophilic carrier with selected weight ratios in 0.1 N hydrochloric acid (HCl). Solid dispersions of carvedilol were prepared successfully using different hydrophilic carriers (mannitol, lactose, and polyethylene glycol [PEG] 4000) as solubilizer by solvent evaporation method. The prepared solid dispersions were evaluated for their physicochemical and micrometric characteristics such as physical appearance, Fourier transform infrared (FTIR), flow properties, drug content, and in vitro drug release studies. Results and Discussion: This research work has been made to enhance the solubility of pure drug of carvedilol using different hydrophilic carriers by converting pure drug into micronized form by solid dispersion technique. The FTIR spectroscopy was used to confirm compatibility and to rule out any possible interaction between drug and hydrophilic carriers used. Nine solid dispersion formulations (CMSD1, CMSD2, CMSD3, CLSD1, CLSD2, CLSD3, CPSD1, CPSD2, and CPSD3) consisting pure drug of carvedilol with mannitol, lactose, and PEG 4000 used as solubilizer in the ratios of 1:1, 1:2, and 1:4, respectively, were prepared. In vitro drug release from solid dispersions was carried out in 0.1N HCl, and the data obtained were fit into different equations and kinetic models to explain release kinetics. A 4.13, 4.60, and 10.7 folds increase in the dissolution efficiency (DE20) of carvedilol was observed with solid dispersions CMSD3, CLSD3, and CPSD3, respectively. Carvedilol with PEG 4000 in 1:2 and 1:4 ratio formulations showed better solubility and emerged to be an ideal formulation for carvedilol solid dispersions. Conclusion: From the study results, it can be concluded that optimized solid dispersion formulations have better solubility as compared to pure drug. The solubility of carvedilol was increasing with increase in the concentration of hydrophilic carriers. The developed solid dispersion of carvedilol with PEG 4000 found useful to enhance solubility of carvedilol.